Characterization of dissolved organic nitrogen in leachate from a newly established and fertilized turfgrass. (15th March 2018) - Lusk, Mary G.; Toor, Gurpal S.; Inglett, Patrick W.
Abstract: Understanding the mechanisms of nitrogen (N) retention and loss from fertilized urban turfgrass is critical to develop practices that mitigate N transport and protect water quality in urban ecosystems. We investigated the fate of N in lysimeters sodded with St. Augustine turfgrass and amended with labeled 15 N from either ammonium sulfate or urea. Fourier transform ion cyclotron resonance mass spectroscopy (FTICR-MS) was employed to identify various biomolecular classes in the leached dissolved organic N (DON) from one lysimeter for each treatment and the control. Mean DON concentrations, over 92 days, were 88, 94, and 94% of total N in the leachate from the control, urea, and ammonium sulfate treatments, respectively. Isotopic analysis showed that <3% of N in the leachate originated from newly applied N fertilizer, suggesting that the remainder of the N in the leachate was derived from the lysimeter soil or sod biomass pools. The 15 N fertilizer recovery was greatest in soil (44–48%), followed by sod+thatch (18–33%), grass clippings (10–13%), and leachate (<3%). Despite isotopic evidence of little contribution of N from fertilizers in the leachate, a fraction of ammonium sulfate fertilizer was recovered as DON in the leachate, likely after uptake and conversion of inorganic fertilizer to organic plant exudates and/or microbial byproducts. FTICR-MS identified N-bearing organic molecular formulas in the leachate from urea and ammonium sulfate treatments, providing evidence of N leaching from newly established turfgrass of DON compounds in a range of biomolecular compositions such as lipid-, protein-, carbohydrate-, and lignin-like molecules. Graphical abstract: Highlights: Nitrogen forms in leachate from a newly established 15 N amended turfgrass were studied. Dissolved organic N was 88–94% of total N leached from lysimeters. Less than 3% of total N in leachate was derived from fertilizers. FTICR-MS revealed lipid-, protein-, carbohydrate-, and lignin-like molecules in leached DON.